



 
Hi Joe. One really useful thing to train yourself to recognize is when you have a "difference of squares", because it factors. In your question, part of it is (x^{2}  1) which is the difference of two perfect squares (x^{2} is obviously a perfect square and so is 1). Whenever you have a difference of squares, it factors to the two roots added times the two roots subtracted. In its general form, this means (a^{2}  b^{2}) = (a +b)(a  b). For example, (8^{2}  3^{2}) = 64  9 = 55, right? Well so does (8 + 3)(8  3). It even works with negative numbers and fractions: (0.4^{2}  (2)^{2}) = 0.16  4 = 3.84 and (0.4 + (2))(0.4  (2)) = (1.6)(2.4) = 3.84 So if you factor (x^{2}  1) you will get (x+1)(x1). Now if you also factor 6x6, you will see what to do next. Hope this helps, Stephen La Rocque.  


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences. 